ETHICAL CONCERNS IN AI-GENERATED SCULPTURAL ART - Sarna, Shilpi; Arora, Neha; Sharma, Rajeev; Karunakaran, Manivannan; Patil, Shashikant; Tiwari, Ranjana; Ingale, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The accelerated development of AI-created sculptural works has set new standards of creativity, authors, and expression of material, but it also delivers some serious ethical issues, questionable by conventional artistic and cultural paradigms. As the roles of generative models, mesh networks in 3D and computational fabrication tools continue to be integrated into the sculptural ideation and production processes, questions of authenticity of the sculptural intent, the validity of the hybrid human machine authorship arises as well as the risk of losing the craft-based knowledge systems. The transparency of AI algorithms also causes ethical concerns that the algorithm might include some sort of hidden bias that form the formal aesthetics, cultural themes, or symbolic forms in a manner that unintentionally misrepresents or steals heritage traditions. Additionally, culturally significant, or proprietary art, is frequently presented as a part of a training dataset, and understandings of the intellectual property rights, permission, and ethical obligations of the creators and institutions using such systems may be disputed. The second ethical factor is that the AI-generated sculptures can be commodified and scaled at a mass level, thereby causing disruptions in the socio-economic ecosystems of sculptors, teachers, designers, and local craft communities. At the same time, the standardization of the algorithmic optimization poses a danger of homogenization of art diversity, thus reducing pluralism of expression of sculptures between cultures. Additional environmental aspects such as the energy requirements of training models as well as the material disposal of rapid prototyping makes the issue of AI-driven sculptural practices even more consequential. This abstract shows the necessity to create transparent, accountable, and culturally respectful AI models that would be able to protect human creativity, the integrity of the arts, and fair co-existence between technological innovation and ancient sculptural arts.